The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1074/jbc.m310958200
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an Intact Noncovalent Homotrimer of Detergent-solubilized Rat Microsomal Glutathione Transferase-1 by Electrospray Mass Spectrometry

Abstract: Microsomal glutathione transferase-1 (MGST1) is a membrane-bound enzyme involved in the detoxification of xenobiotics and the protection of cells against oxidative stress. The proposed active form of the enzyme is a noncovalently associated homotrimer that binds one substrate glutathione molecule/trimer. In this study, this complex has been directly observed by electrospray mass spectrometry analysis of active rat liver MGST1 reconstituted in a minimum amount of detergent. The measured mass of the homotrimer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…The development of strategies to tackle this field is challenging, primarily because the large quantities of detergent suppress the protein signal, whereas the poor solubility of membrane proteins in aqueous buffers often causes the electrospray needle to block. To date only a few MS studies have reported the observation of membrane proteins or their complexes by MS (35)(36)(37)(38)(39). Here we report on the use of a miniaturized form of ES with reduced flow rates (nano-ES), and a high collision energy that facilitates the desolvation process and induces dissociation of detergentproteins clusters, to determine the oligomeric state of an integral homomeric membrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…The development of strategies to tackle this field is challenging, primarily because the large quantities of detergent suppress the protein signal, whereas the poor solubility of membrane proteins in aqueous buffers often causes the electrospray needle to block. To date only a few MS studies have reported the observation of membrane proteins or their complexes by MS (35)(36)(37)(38)(39). Here we report on the use of a miniaturized form of ES with reduced flow rates (nano-ES), and a high collision energy that facilitates the desolvation process and induces dissociation of detergentproteins clusters, to determine the oligomeric state of an integral homomeric membrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we were able to perform a mass spectrometric analysis of intact MGST1 confirming the oligomeric structure and establishing that this technique was applicable to a membrane protein [23]. Technological improvements in the form of an automated nanoelectrospray method capable of high spray stability in the analysis of non-covalent complexes has now allowed us to study MGST1 ligand interactions by this technique demonstrating three bound GSH molecules per trimer.…”
mentioning
confidence: 89%
“…While a vacuum can be regarded as hydrophobic and therefore a suitable environment in which to study such proteins [75], transferring them intact into the mass spectrometer has been a challenge. The first approach which brought success was to prepare a protein in a concentration of a detergent sufficient to solubilize the exposed hydrophobic surfaces, but not so high as to obscure the signal corresponding to protein [76]. …”
Section: The Development Of Ms For Structural Biologymentioning
confidence: 99%